High school students’ attitudes toward mathematics and its relation to mathematics learning achievement - Khairiani Idris; Khazila Khazila; Agustina Agustina; Lisa Lisa (Jurnal Riset Pendidikan Matematika, 2021)
Attitudes toward mathematics have been acknowledged among factors related to students’ mathematics learning achievement. The positive attitudes may decrease when the education level getting higher. This study applied a mixed-method approach to describe students’ attitudes toward mathematics and to analyze the correlation between attitudes toward mathematics and mathematics learning achievement among students in the coastal area of Aceh Province, specifically in Lhokseumawe City and North Aceh Regency. Total of 481 eleventh graders completed attitudes toward mathematics questionnaire online and 19 of them were involved in semi-structured interview. Data of mathematics learning achievement was obtained from students’ scores in their report card of the previous semester. Data analyses were conducted by using Spearman’s correlation and chi-square test. The results of the study revealed that attitudes toward mathematics have a weak negative correlation but significant with mathematics learning achievement. This shows that there is a small percentage of students who have low learning achievement in mathematics tend to have a positive attitude towards mathematics in the high category, while students with high achievement on the contrary. Based on the results of the study, we provide several suggestions regarding learning mathematics and the direction of further research.